Size limit on the formation of periodic mesoporous organosilicas (PMOs) - Rebbin, Vivian; Rothkirch, André; Ohta, Noboru; Hikima, Takaaki; Funari, Sérgio S (Langmuir, 2014)
The decrease of the lattice size of periodic mesoporous organosilicas (PMOs) is one important goal in obtaining a microporous material for storage or adsorption of small molecules. To determine the influence of different synthesis parameters in the lattice size, here we performed in situ small-angle X-ray diffraction studies and show that a variation of the surfactant's headgroup size is not directly followed by the lattice parameter of the resulting structure. We show that in the surfactant series of penta-, hexa-, hepta-, octa-, nona-, and decaethylene glycol monododecyl ether (C12(EO)n, n = 5, 6, 7, 8, 9, 10) the lattice size decreases between n = 5 and n = 8 and then increases, while the ordering of the materials is always cubic (space group Fd3m). This size effect is due to the ethylene oxide (EO) chain conformation that changes as the number of EO groups increases. Short ethylene oxide chains tend to have a so-called "zigzag" conformation while an increase of the chain length leads to a "Mäander" (coiling) conformation. Although this phenomenon is most commonly observed for chains consisting of more than 10 ethylene oxide units, we found a minimum PMO lattice size for 8 EO units and intermediate values for 6 and 7 EO units. The increase of the lattice parameter for more than 9 EO units is attributed to the increasing number of "Mäander" configurated EO units.